Digging for due diligence: The case of non-state mineral supply chain regulation by ITSCI in Rwanda. Issue 3 (September 2021) - Postma, Hester; Geenen, Sara; Partzsch, Lena
Highlights: We study whether non-state actors can hold private actors to account for their actions. We provide insight in the functioning of a due diligence programme on the ground. We research the ITSCI programme in Rwanda, based on interviews and observations. We found several challenges regarding programme implementation. We conclude non-state actors can hold private actors to account on four conditions. Abstract: Today's complex mineral supply chains make it difficult to hold private actors to account in case they breach regulations. Non-state actors increasingly make efforts to help regulate these mineral supply chains via due diligence programmes. The purpose of this study is to investigate how non-state mineral supply chain regulation functions on the ground, and whether and under what conditions non-state actors can hold private actors to account. Based on an in-depth case study of the ITSCI programme in Rwanda, we demonstrate that although non-state regulation of mineral supply chains has huge potential, the ITSCI programme faces several challenges. We find that there are four conditions to be met for non-state actors to hold private supply chain actors to account: 1) the programme should provide clear and timely information to all stakeholders; 2) high-quality and frequent monitoring should be ensured; 3) there should be a possibility of imposing credible sanctions; and 4) the governance of the programme should act in the public interest. On the basis of our research it is reasonable to conclude that the ITSCI programme meets the third condition on sanctions, but that it faces a number of challenges with respect to the first, second and fourth condition.